Design and Implementation of Smart Petrol Station - Baqir, Zahraa M.; Abdali, Mayasah R.; Al-Asady, Heba Abdul-Jaleel (Basrah Journal for Engineering Sciences, 2024)
The problem that still exists nowadays with the petrol station is the method of operation because the petrol station is currently operated manually. As it is a time-consuming process that increases manpower, other problems are related to accuracy, gasoline smuggling, fluctuations in global oil prices, sales, database management, environmental pollution and others. Traditional methods of monitoring fuel in petrol station by humans on site are unable to meet the expectations for efficiency, accuracy and cost. Therefore, this paper designs an intelligent system of three filling stations, where the three stations are simultaneously displayed on a single web application, and this IoT-based system is implemented to address all the problems. Therefore, this paper presents the design and implementation of three petrol stations in which we are going to measure the level of fuel and show it to central server. internet of things (IoT) based petrol station monitoring system is a good approach to improve monitoring efficiency and to improve management efficiency in stations remotely. simulation results presented in LabVIEW software showed the ability of the system to monitor levels of petrol, detect fire, evaporation and etc.